INTERNALIZATION OF THE VALUE OF USWATUN HASANAH AMONG PROSPECTIVE ISLAMIC RELIGIOUS EDUCATION TEACHERS: AN ANALYSIS OF THE INFLUENCE OF SPIRITUAL SELF-EFFICACY AND THE TAZKIYATUN NAFS STRATEGY - Nurvina Laelatul Nikmah; Ahmad Arifi; Nur Hidayat (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to analyze the internal mechanisms that shape exemplary behavior (Uswatun Hasanah) among prospective Islamic Religious Education (PAI) teacher students. Using a mixed methods approach with a Concurrent Triangulation design, this study integrates a quantitative analysis of the influence of Spiritual Self-Efficacy on Modeling Behavior with a qualitative exploration of Tazkiyatun Nafs (purification of the soul) strategies. The results of the quantitative analysis indicate a very strong and significant relationship (r = 0.987; p < 0.01) between spiritual self-efficacy and exemplary behavior, with an R-squared value of 0.974, indicating that 97.4% of the variation in exemplary behavior can be explained by spiritual self-efficacy. Qualitative findings reveal that the Tazkiyatun Nafs strategy, through the phases of Takhalli (purification from vile traits), Tahalli (adornment with virtuous traits), and Tajalli (attainment of spiritual closeness), functions as a strengthening path that transforms abstract beliefs into authentic, concrete actions. The synergy between Bandura’s social cognitive theory and Al-Ghazali’s Sufi concepts affirms that the formation of the Uswatun Hasanah character is an inside-out process, in which internal spiritual strength is the primary determinant of PAI teachers’ professional integrity.